Increasing obstetric intervention for fetal growth restriction is shifting birthweight centiles: a retrospective cohort study. (5th April 2020) - Selvaratnam, RJ; Davey, M‐A; Mol, BW; Wallace, EM
Abstract : Objective: To assess the impact of increasing obstetric intervention on birthweight centiles. Design: Retrospective cohort study of births in five 2‐year epochs: 1983–84, 1993–94, 2003–2004, 2013–2014 and 2016–2017. Population: 665 205 singleton births at ≥32 weeks' gestation. Setting: All maternity services in Victoria, Australia. Methods: For each epoch, we calculated the birthweight cutoffs defining each birthweight centile at 34, 37 and 40 weeks' gestation. We calculated rates of iatrogenic delivery over time. We then calculated the number of babies whose birthweight would have classified them as ≥3rd centile based on 1983–84 centile definitions but as <3rd centile based on 2016–2017 centile definitions. Main outcome measures: Birthweight centile, and gestation at delivery. Results: From 1983–84 to 2016–2017, the rate of iatrogenic delivery for singleton pregnancies increased at all term gestations: 1.6–6.4% at 37 weeks', 4.5–18.3% at 38 weeks', 7.6–23.9% at 39 weeks' and 18.4–25.1% at 40 weeks' (all P  < 0.001). Over the same period, the birthweight cutoffs defining the 3rd, 5th and 10th centiles increased significantly at term, but not preterm, gestations. This led to increasing numbers of term births being classified as small for gestational age (SGA). Of the 2748 babies born in 2016–2017 at 37–39 weeks' gestation with a birthweight <3rd centile in that period, 1478 (53.8%) would have been classified as ≥3rd centile based on 1983–84 centile definitions. Conclusion: Increasing intervention is shifting the birthweight cutoffs that define birthweight centiles and thereby redefining what constitutes SGA. This undermines the use of population‐derived birthweight centiles to audit clinical care. Tweetable abstract: Increasing obstetric intervention is shifting birthweight centiles and therefore definitions of normality. Tweetable abstract: Increasing obstetric intervention is shifting birthweight centiles and therefore definitions of normality.